Moral Singularity, Consciousness, and Artificial Intelligence in The Algorithmic Age of Islamic Economics, Finance, Society, and Science - Choudhury, Masudul Alam; Hoque, Muhammad Nazmul; Zakaria, Nor Balkish; Erum, Naila (Institut Agama Islam Negeri Ponorogo, 2025)
This paper analytically argues that received scientific doctrine and Islamic scholarship, by being methodologically independent of the principle of pairing the moral and material essence of events, have left a significant gap in understanding reality. Such a gap is referred to as exogenously independent, that is, as existing merely as a moral singularity in the methodological worldview of knowledge that otherwise pervades “everything.’ This latter essence pronounces the central role of Tawhid as the pervasiveness of the conscious continuum. The pervasive nature of the conscious continuum in Tawhidi unity of knowledge brings out the analytical power to explain the core of the socio-scientific methodology of pairing (complementarities). This study derives a logical formal model of the interrelations between the centerpiece of the unity of knowledge, consciousness, configuration of epistemic moral-materiality, and socio-scientific intellection in the post-modern algorithmic age. For example, this vastness is inherent in the new epistemic configuration of the AI regime of the algorithmic age. Such an intellectual vista of divinely induced formal inherences in the order of reality is pointed out in this paper as pertaining to the new episteme of socio-scientific moral-materiality holism. A comparative methodological approach was used. The emergent subtle areas of discourse form the originality of the paper, its focus, and its theme.